(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2025)
The research aimed to identify the degree to which primary school principals practice transcendent leadership and organizational agility and the relationship between them. The researcher used the descriptive approach using two questionnaires, the first related to transcendent leadership and the second to organizational agility. The original research community consisted of all teachers working in primary schools "second cycle" in the city of Damascus in the Syrian Arab Republic for the year 2023-2024, and the research sample consisted of (548) male and female teachers, i.e. (27%) of the original community. The sample was selected using a simple random method. The research reached a set of results: the most important of which are: * The degree of application of the dimensions of transcendent leadership by primary school principals with a general average of (3.25) and a standard deviation of (0.74) according to the teachers’ answers and at an average level. The axis that obtained first place was the spirituality axis with a general average of (3.45) and a standard deviation of (0.75), followed by the behavior axis with a general average of (3.29) and a standard deviation of (0.72), and in third place was the values ​​axis with a general average of (3.01) and a standard deviation of (0.76). • The degree of application of the dimensions of organizational agility by primary school principals with a general average of (3.35) and a standard deviation of (0.72) according to teachers’ answers and at an average level. The axis that obtained first place was the axis of agility of practice “application” with a general average of (3.38) and a standard deviation of (0.72), followed by the axis of agility of sensing with a general average of (3.4) and a standard deviation of (0.74), and in third place was the axis of agility of decision-making with a general average of (3.28) and a standard deviation of (0.7). There is a relationship between the degree to which primary school principals practice their role in the dimensions of transcendent leadership and their achievement of the degree of practicing organizational agility from the teachers’ point of view. The most important research proposals are: • Preparing training programs for basic education school administrations, focusing on the areas of possessing transcendent leadership skills and organizational agility by holding training seminars and workshops for them. • The need to pay attention to the spiritual side of workers in educational institutions to develop their personalities and their affiliation to those institutions in order to preserve and develop them. • Conducting a study on the training needs of basic education school principals in light of the two approaches to transcendent leadership and organizational agility.